Neural sensitivity to social reward and punishment anticipation in Social Anxiety Disorder. - Henk eCremers; Ilya eVeer; Philip eSpinhoven; Serge A R Rombouts; Karin eRoelofs (Frontiers in Behavioral Neuroscience, 2015)
An imbalance in the neural motivational system may underlie Social Anxiety Disorder (SAD). This study examines social reward and punishment anticipation in SAD, predicting a valence-specific effect: increased striatal activity for punishment avoidance compared to obtaining a reward. Individuals with SAD (n=20) and age, gender, and education case-matched controls (n=20) participated in a functional magnetic resonance imaging (fMRI) study. During fMRI scanning, participants performed a Social Incentive Delay task to measure the anticipation of social reward and punishment. The left putamen (part of the striatum) showed a valence-specific interaction with group after correcting for medication use and comorbidity. The control group showed a relatively stronger activation for reward vs. punishment trials, compared to the social anxiety group. However, post-hoc pairwise comparisons were not significant, indicating that the effect is driven by a relative difference. A connectivity analysis (Psychophysiological interaction) further revealed a general salience effect: SAD patients showed decreased putamen-ACC connectivity compared to controls for both reward and punishment trials. Together these results suggest that the usual motivational preference for social reward is absent in SAD. In addition, cortical control processes during social incentive anticipation may be disrupted in SAD. These results provide initial evidence for altered striatal involvement in both valence-specific and valence nonspecific processing of social incentives, and stress the relevance of taking motivational processes into account when studying social anxiety.